An unusual cause of cardiogenic shock: tricuspid regurgitation and right ventricular perforation due to vena cava filter migration - Mocavero, P E (EDIMES Edizioni Internazionali Srl, 2012)
Dislocation and migration of the inferior vena cava filter to the right heart is an uncommon but serious complication, requiring prompt diagnosis and appropriate therapy. We report the case of a seventy-year old man, who had previously undergone vena cava filter implantation and who was admitted to the Intensive Care Unit due to acute respiratory distress with the suspect of pneumonia-related sepsis. Due to the worsening of hemodynamics and the development of cardiogenic shock, the patient underwent bedside echocardiography, which on the contrary revealed dislocation of the filter and the entrapment of the device within the tricuspid valve and chordae tendineae. This evidence was confirmed also by the chest-abdominal X-ray. The patient underwent tricuspid valve surgical replacement and successfully recovered. The transthoracic and transesophageal echocardiographies performed in the intensive care unit were able to first orient the diagnostic efforts toward the correct cause.